Household food waste and food security: a review of behavioral, socioeconomic, and educational determinants - Aisy, Nabilah Rihadatul; Rahmawati, Widya; Rahmawati, Irma Sarita (Berita Kedokteran Masyarakat, 2025)
Purpose: This systematic review examines the relationship between household food waste and food security, exploring key behavioral, socio- economic, and educational determinants that shape this interconnection in domestic settings. Methods: The review adhered to PRISMA guidelines and applied Covidence software to screen items obtained from Scopus, Pub- Med, and Web of Science, from 2015 to 2025. Search terms used included "household", "food waste", "food security", and "waste management". Inclusion criteria were based on the PICOS framework, targeting studies that investigated household food waste and food security outcomes using qualitative or quantitative designs. Results: Out of 263 identified articles, 12 met the eligibility criteria. The findings revealed that higher food waste is generally associated with food-secure and high-income households due to excessive purchasing and poor planning. However, food-insecure house- holds also contributed significantly to food waste due to inadequate storage practices and limited food literacy. Behavioral and educational factors, including purchasing habits and levels of awareness, were significant indicators of food waste. Several studies emphasized the role of food and nutrition literacy, proper storage, and community engagement in minimizing food loss and improving food availability. Register of Systematic Reviews (PROSPERO) under registration number CRD420251271753.Conclusion: Household food waste negatively impacts all four dimensions of food secu- rity. Effective strategies should integrate educational interventions, decen- tralized storage technologies, and community-based initiatives to enhance food system resilience. Reducing food waste is necessary to foster ecological health, economic success, and reliable household food security.